2016
DOI: 10.1002/adma.201505617
|View full text |Cite
|
Sign up to set email alerts
|

Evaporative Self‐Assembly of Gold Nanorods into Macroscopic 3D Plasmonic Superlattice Arrays

Abstract: Millimeter-scale 3D superlattice arrays composed of dense, regular, and vertically aligned gold nanorods are fabricated by evaporative self-assembly. The regular organization of the gold nanorods into a macroscopic superlattice enables the production of a plasmonic substrate with excellent sensitivity and reproducibility, as well as reliability in surface-enhanced Raman scattering. The work bridges the gap between nanoscale materials and macroscopic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
158
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(163 citation statements)
references
References 51 publications
5
158
0
Order By: Relevance
“…changed the capping ligand CTAB with negatively charged surfactants to optimize the assembly process for improved GNR arrays. [34] After the exchange,t he z-potential of the GNRs is lowered to about À15.0 mV.I nt his work, they found that not only the orientation of the GNRs assemblies but also the geometry of the arrays can be controlled by regulating GNR surface chemistry,s urfactants,a nd the substrates.I nterestingly,p artially functionalized GNRs can assemble into vertically array with alterative symmetry.Arecent report shows that by introducing Rhodamine 6G to the CTAB bilayer,t etragonal GNR arrays instead of traditional hexagonal arrays have been formed. [35] Finally,amicropatterned substrate was used for directing the GNR self-assembly to form exclusively vertical arrays (Figure 3).…”
Section: Methodsmentioning
confidence: 98%
“…changed the capping ligand CTAB with negatively charged surfactants to optimize the assembly process for improved GNR arrays. [34] After the exchange,t he z-potential of the GNRs is lowered to about À15.0 mV.I nt his work, they found that not only the orientation of the GNRs assemblies but also the geometry of the arrays can be controlled by regulating GNR surface chemistry,s urfactants,a nd the substrates.I nterestingly,p artially functionalized GNRs can assemble into vertically array with alterative symmetry.Arecent report shows that by introducing Rhodamine 6G to the CTAB bilayer,t etragonal GNR arrays instead of traditional hexagonal arrays have been formed. [35] Finally,amicropatterned substrate was used for directing the GNR self-assembly to form exclusively vertical arrays (Figure 3).…”
Section: Methodsmentioning
confidence: 98%
“…But for practical SERS detection, colloidal nanoparticles synthesized by LAL can still be challenges for producing large and stable enhancement of Raman signals, due to the discrete and random distribution of hot spots. [1c] Self‐assembly of metallic nanoparticles arrays onto a substrate are usually executed,[4e,14] whereas the poor adhesive forces to substrates might restrict their practical applications. Recently, incorporating plasmonic structures onto solid substrates by lasers have been intensively studied for applications on reproducible biochemical analysis and diagnostics due to their on‐demand fabrication features, which possess huge potential in practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, numerous detection methods based on fluorescence, atomic absorption spectroscopy, biosensor, colorimetric, and resonance scattering have been developed for the detection of Hg 2+ . However, compared to these methods, surface‐enhanced Raman scattering (SERS) with its extremely high surface sensitivity and fingerprint information about the chemical structures has attracted increasing attention in various areas, including food safety, biology, biomedical diagnostics, and chemistry . Therefore, detecting traces of Hg 2+ ions through SERS has received the welcome of people.…”
Section: Introductionmentioning
confidence: 99%